Guyub Kenclengan Residents: Gaining Social Capital in Village Development - Hidayat, Rochmat (ann4publisher@gmail.com, 2025)
Background. Villages are distinctive entities because they existed before the Unitary State of the Republic of Indonesia was proclaimed. As a social entity, villages have long had a system to organize their communities based on their local wisdom, which directly involves the community. In village communities, local wisdom is shaped by social values and has become part of daily life—cooperation, kinship, deliberation for consensus, and tepa selira (tolerance). The presence of this local wisdom cannot be separated from the religious values embraced by the community, so the values of this local wisdom are increasingly attached to them into a harmonious relationship between social relations, relations with nature and the environment, and with the creator. Aim. This study wants to see how social capital works in the Picking Up Outstanding Duafa activities in Klangenan Village. This activity gathers the village community's self-help, spearheaded by the Rukun Warga Management. Methods. This research method uses qualitative analysis with a case study approach by taking a locus in Klangenan Village, where the activity was carried out with community respondents who interacted with the activity. The theoretical conceptual framework of this research uses Putnam's social capital theory, which describes the work of social capital with the presence of social networking, trust, and empathy. Result. The results of this study show that Guyub Kenclengan's activities in Klangenan Village present a working social capital component. The Community Trust component, which is the donor of the activity to the manager, does not see the formal side of the institution. However, Rukun Warga Management shows its existence and credibility in managing activities before making financial and activity achievement reports. Conclusions. The networking (social network) that has been built has succeeded in uniting the ideas of the Rukun Warga Management and the community about handling environmental and social affairs for the common good and presenting mutually agreed-upon values.